An inconspicuous threat to our nation-it’s time to end - Sivakumar, Abinav; John, Anugraha (International Journal Of Community Medicine And Public Health, 2023)
It is well known that counterfeit medical products cause harm to patients and fail to treat the diseases for which they were intended. They lead to loss of confidence in medicines, healthcare providers and health systems. They are becoming common in every region of the world. It is believed that up to 10% of all medicines sold worldwide are counterfeit, with higher prevalence in regions where drug regulatory and enforcement systems are weakest. An estimated 1 in 10 medical products in low- and middle-income countries and it contributes to antimicrobial resistance and drug-resistant infections.